2016
DOI: 10.1103/physrevb.94.104514
|View full text |Cite
|
Sign up to set email alerts
|

Shubnikov-de Haas quantum oscillations reveal a reconstructed Fermi surface near optimal doping in a thin film of the cuprate superconductorPr1.86Ce0.14CuO4±δ

Abstract: We study magnetotransport properties of the electron-doped superconductor Pr2−xCexCuO 4±δ with x = 0.14 in magnetic fields up to 92 T, and observe Shubnikov de-Haas magnetic quantum oscillations. The oscillations display a single frequency F =255±10 T, indicating a small Fermi pocket that is ∼ 1% of the two-dimensional Brillouin zone and consistent with a Fermi surface reconstructed from the large hole-like cylinder predicted for these layered materials. Despite the low nominal doping, all electronic propertie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 42 publications
6
14
0
Order By: Relevance
“…Our FS area values are also comparable to those seen in PCO films [25]. Compared to recently published results on PCCO films of x=0.14 [21], where the frequency is 255 T and m e =0.43, our PCCO x=0.15 data disagree substantially. However, note that near optimal doping, a hump is typically observed in the MR, and the absence of such a feature suggests that the sample in [9] actually may have a doping level comparable to our x=0.16 sample, which has no hump.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Our FS area values are also comparable to those seen in PCO films [25]. Compared to recently published results on PCCO films of x=0.14 [21], where the frequency is 255 T and m e =0.43, our PCCO x=0.15 data disagree substantially. However, note that near optimal doping, a hump is typically observed in the MR, and the absence of such a feature suggests that the sample in [9] actually may have a doping level comparable to our x=0.16 sample, which has no hump.…”
Section: Resultssupporting
confidence: 80%
“…Rather than measuring the unreconstructed FS, magnetic breakdown involving tunneling between the electron and hole pockets was suggested to be responsible for the high frequency oscillations [19]. Additionally, Breznay et al observed SdH oscillations of the in-plane MR in PCCO thin films (x≈x o , x=0.14) [21]. However, only the small hole pockets are observable in quantum oscillations for both PCCO and NCCO at x 0 .…”
Section: Introductionmentioning
confidence: 99%
“…3F), which is consistent with our inability to observe a gap beyond x=0. 16. Such a behavior of gap closing near x=0.16~0.17 is consistent with a quantum critical point (QCP) in that doping range, as suggested by a x to 1-x density transition in transport experiments (13,18,19).…”
Section: Resultssupporting
confidence: 80%
“…Both the back-bending behavior (folded band) and gap opening have been observed at all doping levels we measured (x=0.11, x=0.15, x=0. 16), demonstrating that the FS reconstruction persists to the over-doped regime. This is consistent with QOM (12)(13)(14)(15)(16)(17), and the well-defined gap suggests that a magnetic breakdown in QOM is less likely below x=0.16.…”
Section: Resultsmentioning
confidence: 91%
“…Quantum oscillations have also been observed in underdoped HgBa 2 CuO 4+δ [63,64], with frequency 840T corresponding to about 3% of the Brillouin zone, or 0.061 carriers per pocket. Several other such observations in hole-doped cuprates have been reported [65][66][67]. Whether these oscillations are due to hole pockets or electron pockets or both has been controversial [68,69] and is unsettled.…”
Section: Quantum Oscillationsmentioning
confidence: 99%